Sarah Waller’s Help-Seeking Model: Understanding African American Women Intimate Partner Violence Survivors’ Help-seeking Process - Waller, Bernadine (Journal of interpersonal violence, 2023)
African American women overwhelmingly experience the poorest outcomes resulting from intimate partner violence (IPV) victimization. Despite theoretical advancements, there remain a paucity of theories that explicate this marginalized population’s comprehensive help-seeking process that includes the domestic violence service provision system and the Black church. We conducted 30 in-depth, semi-structured interviews with women who self-identified as African American. We utilized sensitizing concepts from the Transtheoretical Model of Change and Intersectionality theories, along with Agency framework and employed constructivist grounded theory methodology. Sarah’s Help-Seeking Model emerged from the data and includes nine phases: (1) Awareness, (2) Acknowledgment, (3) Assessment, (4) Enough, (5) Enlist, (6) Escalate, (7) Reject, (8) Resolve, and (9) Restoration. This is the first theory that identifies how this vulnerable and underserved population’s mental health and social support-seeking process is partially mediated by mistrust of law enforcement, disappointment in linkage to care and services, fear of death, and willingness to survive.